Activation of electrospun lignin-based carbon fibers and their performance as self-standing supercapacitor electrodes - García-Mateos, Francisco José; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Morallón, Emilia; Cazorla-Amorós, Diego; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (Elsevier, 2020)
The production and activation of self-standing carbon electrodes from electrospun lignin fibers was analyzed in this work. Carbon microfibers were prepared at 900 °C from air-stabilized spun cloths by direct carbonization under inert atmosphere and with diluted O2. The modifications of the porosity and surface chemistry of the carbon fibers was also studied by adding H3PO4 in the lignin solution and using different oxygen partial pressures during activation. The presence of phosphoric acid not only increases the porosity development and the preparation yield, but also enhances the gravimetric capacitance of the electrodes. In addition, the activation in presence of oxygen increases the surface area and the generation of wider micropores. Microporous carbon fibers with surface areas as high as 2340 m2 g−1 were obtained using this method. The direct conformation of carbon fibers into binderless electrodes allows to achieve high-power rate capability supercapacitors. Activation in presence of oxygen can enhance up to 50% the energy storage of supercapacitors without compromising the power of the device (8.4 Wh kg−1 and Pmax of 47 kW kg−1). However, at high activation degrees, no further gain in energy density is observed due to the excessive widening of micropores, and the loss of electrical conductivity that increases the cell resistance, limiting the power capability of the device. The optimal results in terms of energy, power and durability are achieved combining low amounts of H3PO4 and mild activation with O2, confirming that electrospinning of lignin is a promising method for sustainable production of self-standing supercapacitor electrodes.
Keywords: Electrodos de carbono; Lignin; Supercapacitors; Electrospinning; Carbon fibers